Electrode and power storage device
By employing a composite electrode structure with distinct particle sizes of solid electrolyte near the current collecting layer and on the surface, the issues of surface unevenness and ion diffusion resistance are addressed, enhancing the performance and reliability of power storage devices.
Patent Information
- Application Number
- JP2020207201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-15
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2040-12-15
AI Technical Summary
In existing electrode technologies, the increased proportion of solid electrolyte with large particle size away from the current collecting layer leads to surface unevenness, which can result in shortened electrode distances and concentrated electrode reactions, potentially causing damage such as short circuits.
The electrodes incorporate a composite layer with a current collecting layer, containing a solid electrolyte and an active material, along with an ionic conductive material. The solid electrolyte particles are divided into two groups: one near the current collecting layer with larger particles and another closer to the surface with smaller particles, reducing surface unevenness and enhancing ion diffusion.
This configuration reduces ion diffusion resistance near the current collecting layer, increases the utilization rate of the active material, and minimizes surface unevenness, thereby reducing the risk of damage such as short circuits in power storage devices.
Smart Images

Figure 0007666918000001 
Figure 0007666918000002 
Figure 0007666918000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode and an electricity storage device. [Background technology]
[0002] Electrodes including a composite layer including an active material and a solid electrolyte, and a current collecting layer are known. The electrode of the electricity storage device disclosed in Patent Document 1 mixes a solid electrolyte with a small particle size and a solid electrolyte with a large particle size in the composite layer, smoothing the movement of ions between the solid electrolyte and the active material and ensuring the utilization rate of the active material. Furthermore, the proportion of the solid electrolyte with a small particle size near the current collecting layer in the composite layer is increased, and the porosity of the composite layer near the current collecting layer is increased, suppressing the expansion and contraction of the electrode during charging and discharging. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2014 / 132333 Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the technology of Patent Document 1, the composite layer has a large proportion of solid electrolyte with large particle size as it moves away from the current collecting layer, so the surface becomes uneven. When the electrodes are placed facing each other, the convex parts of the composite layer tend to shorten the distance between the electrodes, and the electrode reaction tends to concentrate in the convex parts of the composite layer, which may cause damage such as a short circuit.
[0005] The present invention has been made to solve this problem, and has an object to provide an electrode and an electricity storage device that can increase the utilization rate of the active material while reducing damage to the electricity storage device. [Means for solving the problem]
[0006] To achieve this object, the electrode of the present invention includes a current collecting layer and a composite layer, and the composite layer includes a solid electrolyte and an active material. The composite layer further includes an ion conductive material in contact with the solid electrolyte and the active material. The particle group consisting of the solid electrolyte and the active material includes a first group arranged at a position including the interface between the current collecting layer and the composite layer, and a second group arranged at a position including the surface of the composite layer and located between the first group and the surface of the composite layer, and the first group contains a large amount of solid electrolyte having a particle size larger than that of the solid electrolyte included in the second group. The power storage device of the present invention includes the electrode. Effect of the Invention
[0007] According to the first aspect, the first group of particles of solid electrolyte and active material, which is arranged at a position including the interface between the current collecting layer and the composite layer, contains a large amount of solid electrolyte particles having a larger particle diameter than the solid electrolyte particles contained in the second group, which is arranged at a position including the surface of the composite layer and located between the first group and the surface of the composite layer. Therefore, ions are more likely to diffuse within the solid electrolyte particles near the current collecting layer. The ion conductive material is in contact with the solid electrolyte and the active material, so that the resistance caused by the movement of ions between the solid electrolyte and the active material contained in the first group can be reduced, and the utilization rate of the active material can be increased.
[0008] On the other hand, the second group, which is disposed at a position including the surface of the composite layer, contains a large amount of solid electrolytes with smaller particle diameters than the solid electrolytes contained in the first group, so the surface of the composite layer is less uneven. Since the electrode reaction occurs dispersedly on the surface of the composite layer, damage to the electricity storage device in which the electrodes are disposed can be reduced.
[0009] According to the second aspect, the solid electrolyte particles in the first group have a larger number of particles with a particle size of 1 μm or more than the solid electrolyte particles in the second group, and the solid electrolyte particles in the second group have a larger number of particles with a particle size of less than 1 μm than the solid electrolyte particles in the first group. This makes it easier for ions to diffuse within the solid electrolyte particles near the current collecting layer. Thus, in addition to the effect of the first aspect, the utilization rate of the active material can be increased. Furthermore, the surface irregularities of the composite layer are reduced, so damage to the electricity storage device can be reduced.
[0010] According to the third aspect, when the solid electrolyte is an oxide, the stability against humidity can be improved. Although the oxide solid electrolyte has a large grain boundary resistance, the composite layer includes an ion conductive material in contact with the solid electrolyte and the active material, and therefore, in addition to the effects of the first or second aspect, the grain boundary resistance of the composite layer can be reduced and the stability against humidity can be improved.
[0011] According to the fourth aspect, the ionic conductive material contains an ionic liquid that has high wettability and high heat resistance with respect to the solid electrolyte, and thus in addition to the effects of any one of the first to third aspects, it is possible to reduce the resistance caused by the movement of ions between the solid electrolyte and the active material and ensure the heat resistance of the electrode.
[0012] According to the fifth aspect, the volume of the active material in the first group is smaller than the volume of the active material in the second group. This results in a greater amount of solid electrolyte and ionic conductive material in the first group than in the second group, making it possible to reduce the difference between the utilization rate of the active material in the first group and the utilization rate of the active material in the second group. In addition to the effects of any one of the first to fourth aspects, the electrode is less susceptible to deterioration.
[0013] According to the sixth aspect, the same effect as any one of the first to fifth aspects is obtained. [Brief description of the drawings]
[0014] [Figure 1] 1 is a cross-sectional view of an electricity storage device according to an embodiment. [Diagram 2] FIG. 2 is a cross-sectional view of a positive electrode layer. [Diagram 3] FIG. 2 is a cross-sectional view of a negative electrode layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, preferred embodiments of the present invention will be described with reference to the accompanying drawings. Fig. 1 is a schematic cross-sectional view of an electricity storage device 10 in one embodiment. The electricity storage device 10 in this embodiment is a secondary battery, and is a lithium ion solid-state battery in which the power generation element is made of a solid. The power generation element being made of a solid means that the skeleton of the power generation element is made of a solid, and does not exclude, for example, a form in which the skeleton is impregnated with a liquid.
[0016] 1, the electricity storage device 10 includes, in this order, a positive electrode layer 11, a solid electrolyte layer 28, and a negative electrode layer 31. The positive electrode layer 11 and the negative electrode layer 31 are electrodes of the electricity storage device 10. The positive electrode layer 11, the solid electrolyte layer 28, and the negative electrode layer 31 are housed in a case (not shown).
[0017] Fig. 2 is a schematic cross-sectional view of the positive electrode layer 11. The positive electrode layer 11 is formed by overlapping a current collecting layer 12 and a composite layer 13. Fig. 2 shows a cross section of the positive electrode layer 11 perpendicular to an interface 14 between the current collecting layer 12 and the composite layer 13. The current collecting layer 12 is a member having electrical conductivity. Examples of materials for the current collecting layer 12 include metals selected from Ni, Ti, Fe, and Al, alloys containing two or more of these elements, stainless steel, and carbon materials.
[0018] The composite layer 13 includes a solid electrolyte 15, an active material 18, and an ion conductive material 21. The solid electrolyte 15 is a solid material that conducts carrier ions. The solid electrolyte 15 includes one or more materials selected from oxides, sulfides, hydrides, and organic materials. An oxide-based solid electrolyte 15 is preferable because it has high stability against humidity. The solid electrolyte 15 may be a composite of an oxide, a hydride, or the like.
[0019] Examples of the oxide-based solid electrolyte 15 include oxides having a garnet-type structure or a garnet-like structure containing at least Li, La, and Zr, oxides having a NASICON-type structure, and oxides having a perovskite structure.
[0020] Garnet-type oxides have the basic composition Li5La3M2O 12(M=Nb, Ta). Oxides with garnet-type or garnet-like structures containing at least Li, La, and Zr are Li7La3Zr2O, in which pentavalent M cations are replaced by tetravalent cations. 12 or Li7La3Zr2O 12 Examples include those in which the element substitution of Mg and Sr is performed on the above.
[0021] In particular, a solid electrolyte containing Li, La, Zr, Mg, and Sr and having a garnet-type crystal structure is preferable because it has a smaller intragranular resistance than other oxides. The solid electrolyte containing Li, La, Zr, Mg, and Sr and having a garnet-type crystal structure is, for example, one in which the molar ratio of each element satisfies at least one of the following (1) and (2). (1) 1.33≦Li / (La+Sr)≦3, 0≦Mg / (La+Sr)≦0.5, and 0≦Sr / (La+Sr)≦0.67. (2) 2.0≦Li / (La+Sr)≦2.5, 0.01≦Mg / (La+Sr)≦0.14, and 0.04≦Sr / (La+Sr)≦0.17.
[0022] Oxides having a NASICON structure include oxides containing at least Li, M (wherein M is one or more elements selected from Ti, Zr, and Ge) and P, such as Li(Al,Ti)2(PO4)3 and Li(Al,Ge)2(PO4)3. Oxides having a perovskite structure include oxides containing at least Li, Ti, and La, such as La 2 / 3-X Li 3X An example is TiO3.
[0023] The sulfide-based solid electrolyte 15 is a crystalline thiolithium type, Li 10 GeP2S 12 type, argyrodite type, Li7P3S 11Examples of the hydride-based solid electrolyte 15 include a solid solution of LiBH4 with a lithium halide compound (LiI, LiBr, LiCl) and lithium amide (LiNH2). Examples of the organic solid electrolyte 15 include polyethylene oxide, polypropylene oxide, and polyacrylonitrile.
[0024] The active material 18 is exemplified by a metal oxide having a transition metal, a sulfur-based active material, and an organic active material. The metal oxide having a transition metal is exemplified by a metal oxide containing Li and one or more elements selected from Mn, Co, Ni, Fe, Cr, and V. The metal oxide having a transition metal is exemplified by LiCoO2, LiMn2O4, LiNiVO4, LiMn 1.5 Ni 0.5 Examples include O4 and LiFePO4.
[0025] In order to suppress the reaction between the active material 18 and the solid electrolyte 15, a coating layer can be provided on the surface of the active material 18. The coating layer can be made of Al2O3, ZrO2, LiNbO3, Li4Ti5O 12 , LiTaO3, LiNbO3, LiAlO2, Li2ZrO3, Li2WO4, Li2TiO3, Li2B4O7, Li3PO4 and Li2MoO4 are examples.
[0026] Examples of sulfur-based active materials include S, TiS2, NiS, FeS2, Li2S, MoS3, and sulfur-carbon composites. Examples of organic active materials include radical compounds such as 2,2,6,6-tetramethylpiperidinoxyl-4-yl methacrylate and polytetramethylpiperidinoxyl vinyl ether, quinone compounds, radialene compounds, tetracyaquinodimethane, and phenazine oxide.
[0027] The ion conductive material 21 includes at least one selected from a liquid, a gel, and a solid that conduct carrier ions. The ion conductive material 21 is in contact with the solid electrolyte 15 and the active material 18, and is a medium through which ions move.
[0028] The ionic conductive material 21 made of liquid is exemplified by an organic solvent in which an electrolyte salt is dissolved, and an ionic liquid in which an electrolyte salt is dissolved. When the carrier ion is Li ion, examples of the electrolyte salt include LiBF4, LiPF6, LiClO4, CF3SO3Li, LiN(SO2CF3)2, LiN(SO2F)2, and LiN(SO2C2F5)2. Examples of the organic solvent include ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and methyl ethyl carbonate.
[0029] Examples of ionic liquids include those having, as the cation, ammonium-based cations such as butyltrimethylammonium and trimethylpropylammonium; imidazolium-based cations such as 1-ethyl-3-methylimidazolium and 1-butyl-3-methylimidazolium; piperidinium-based cations such as 1-butyl-1-methylpiperidinium and 1-methyl-1-propylpiperidinium; pyridinium-based cations such as 1-butyl-4-methylpyridinium and 1-ethylpyridinium; pyrrolidinium-based cations such as 1-butyl-1-methylpyrrolidinium and 1-methyl-1-propylpyrrolidinium; sulfonium-based cations such as trimethylsulfonium and triethylsulfonium; phosphonium-based cations; and morphonium-based cations.
[0030] Ionic liquids contain Cl as an anion. - , Br - Halides such as BF4 - Boron compounds such as (NC)2N - , (CF3SO2)2N - , (FSO2)2N - Amine series such as CH3SO4 - Sulfate series such as CF3SO3 - Sulfonate series such as PF6 - Examples include those having a phosphoric acid system such as the above.
[0031] Examples of the ionic liquid include butyltrimethylammonium bis(trifluoromethanesulfonyl)imide, trimethylpropylammonium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-methyl-1-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-methyl-1-propylpyrrolidinium bis(fluorosulfonyl)imide, and 1-methyl-1-propylpiperidinium bis(fluorosulfonyl)imide.
[0032] The ionic conductive material 21 made of gel is, for example, a polymer gel in which an organic solvent (plasticizer) is added to a polymer and an electrolyte is added to the polymer gel. Examples of the polymer gel include polyethylene oxide, polymethyl methacrylic acid, polyacrylonitrile, and a copolymer of vinylidene fluoride and propylene hexafluoride.
[0033] The solid ion conductive material 21 is a solid electrolyte that is softer than the solid electrolyte 15 and the active material 18. When the solid electrolyte 15 is an oxide-based one, the solid ion conductive material 21 can be exemplified by a hydride-based solid electrolyte, and when the carrier ion is a Li ion, by a lithium halide compound such as LiI.
[0034] The composite layer 13 may further include a binder and a conductive assistant. Examples of the binder included in the composite layer 13 include polyimide-based, acrylic-based, polysiloxane, polyalkylene glycol, polyvinylidene fluoride, polytetrafluoroethylene, and ethylene-vinyl alcohol copolymer. Examples of the conductive assistant included in the composite layer 13 include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.
[0035] The solid electrolyte 15 contained in the composite layer 13 includes first particles 16 and second particles 17. The first particles 16 are particles having a larger particle size than the second particles 17. The particle size of the particles 16, 17 refers to the circle equivalent diameter (the diameter of a circle having the same area as the cross-sectional area of the particles 16, 17). For example, the particle size of the first particles 16 is 1 μm or more and is ½ or less of the thickness of the composite layer 13. The particle size of the second particles 17 is less than 1 μm. In the composite layer 13, many of the first particles 16 are arranged near the current collecting layer 12, and many of the second particles 17 are arranged in positions far from the current collecting layer 12.
[0036] The particle group composed of solid electrolyte 15 and active material 18 contained in composite layer 13 includes a first group 23 arranged at a position including interface 14 between current collecting layer 12 and composite layer 13, and a second group 24 arranged at a position including surface 22 of composite layer 13. Second group 24 is located between first group 23 and surface 22. In this embodiment, the particle group contained in composite layer 13 consists of first group 23 and second group 24.
[0037] The solid electrolyte layer 28 (see FIG. 1) is in contact with the surface 22 of the composite layer 13. The solid electrolyte layer 28 contains a solid electrolyte. The solid electrolyte layer 28 may further contain an ionic liquid in which an electrolyte salt is dissolved. The solid electrolyte and ionic liquid contained in the solid electrolyte layer 28 are similar to the solid electrolyte 15 and ionic liquid contained in the positive electrode layer 11, and therefore a description thereof will be omitted.
[0038] The straight lines 25, 26 shown in Fig. 2 are lines drawn on an image of the composite layer 13 acquired by a scanning electron microscope (SEM). To ensure the measurement accuracy of the numbers A and B of intersections (described later), the lengths of the straight lines 25, 26 are 50 µm or more and the widths are 1 µm or less. If an image is obtained in which straight lines 25, 26 with a length of 50 µm or more cannot be drawn, the longest straight lines 25, 26 are drawn on that image. The magnification of the image acquired by the SEM can be, for example, 3000 times.
[0039] Of the active materials 18 contained in the composite layer 13, the particles 19 are those whose geometric center of a cross section is closest to the current collecting layer 12. In this embodiment, the particles 19 are in contact with the current collecting layer 12. The particles 19 are included in a first group 23. The particles 20 are those whose geometric center of a cross section is farthest from the current collecting layer 12, among the active materials 18 contained in the composite layer 13. The particles 20 are included in a second group 24.
[0040] The surface 22 of the composite layer 13 is a straight line passing through a point that is the furthest from the interface 14 among the lines indicating the grain boundaries of the particles 20, and is a straight line parallel to the interface 14. The straight line 25 is a straight line passing through the geometric center of the particle 19 and is a straight line parallel to the interface 14. The straight line 26 is a straight line passing through the geometric center of the particle 20 and is a straight line parallel to the interface 14. The straight line 25 crosses the first group 23, and the straight line 26 crosses the second group 24.
[0041] Line 27 is a line drawn at the boundary between first group 23 and second group 24, and is a line parallel to interface 14. Solid electrolyte 15 and active material 18 that intersect with line 27 are excluded from the particles contained in first group 23 and second group 24. Line 27 exists in the center range of three ranges obtained by dividing the distance between interface 14 and surface 22 of composite layer 13 into three equal parts.
[0042] The first group 23 contains more first particles 16 than second particles 17. The second group 24 contains more second particles 17 than first particles 16. That is, the first group 23 contains more solid electrolytes 15 having a larger particle size than the solid electrolytes 15 contained in the second group 24. This can be determined by comparing the particle size distribution of the circle-equivalent diameters of the solid electrolytes 15 contained in the first group 23 with the particle size distribution of the circle-equivalent diameters of the solid electrolytes 15 contained in the second group 24 through image analysis of the cross-section of the composite layer 13.
[0043] Therefore, the number A of intersections between the straight line 25 and the grain boundaries of the solid electrolyte 15 is smaller than the number B of intersections between the straight line 26 and the grain boundaries of the solid electrolyte 15. In particular, it is more preferable that the number B is at least twice the number A. The numbers A and B of intersections are measured for images obtained at five or more positions separated from each other in the composite layer 13. The positive electrode layer 11 satisfies the condition A < B in 80% or more of five or more images, and more preferably satisfies the condition 2A ≤ B.
[0044] The five or more images mean that there are five or more images in which the portion through which the straight line 25 passes and the portion through which the straight line 26 passes are included in one image. However, when an image in which the portion through which the straight line 25 passes and the portion through which the straight line 26 passes are included in one image cannot be obtained, five or more images including the portion through which the straight line 25 passes are prepared, and separately, five or more images including the portion through which the straight line 26 passes are prepared. The numbers A and B are determined from these images.
[0045] In the positive electrode layer 11, the active material 18 is unevenly distributed in the thickness direction of the composite layer 13. Specifically, the volume occupied by the active material 18 in the first group 23 is smaller than the volume occupied by the active material 18 in the second group 24. Therefore, the number C of intersections between the straight line 25 and the grain boundaries of the active material 18 is smaller than the number D of intersections between the straight line 26 and the grain boundaries of the active material 18. Note that the straight lines for measuring the number of points (intersections) intersecting the grain boundaries of the active material 18 are not limited to the straight lines 25 and 26. Two or more straight lines (each having a length of 50 μm or more and a width of 1 μm or less) parallel to the interface 14 and intersecting the grain boundaries of the active material 18 may be used. The number of intersections between a straight line with a longer distance from the interface 14 and the grain boundaries of the active material 18 is larger than the number of intersections between a straight line with a shorter distance from the interface 14 and the grain boundaries of the active material 18.
[0046] The positive electrode layer 11 is manufactured, for example, as follows. First, a first slurry containing the first particles 16, the active material 18, the ion conductive material 21, and a solvent is used as a raw material and tape-cast on the current collecting layer 12. A second slurry containing the second particles 17, the active material 18, the ion conductive material 21, and a solvent is applied onto the tape, and the solvent is volatilized to obtain the positive electrode layer 11. By making the amount of the active material 18 contained in the second slurry greater than the amount of the active material 18 contained in the first slurry, the active material 18 can be unevenly distributed in the thickness direction of the composite layer 13.
[0047] Alternatively, a slurry containing the first particles 16, the second particles 17, the active material 18, the ion conductive material 21, and a solvent may be applied onto the current collecting layer 12 and left in a state where the evaporation of the solvent contained in the slurry is restricted. The time for leaving the slurry is, for example, 5 minutes or more, depending on the viscosity of the slurry. By utilizing the difference in the settling speed of the first particles 16 and the second particles 17 in the slurry, a large amount of the first particles 16 can be distributed near the current collecting layer 12. The solvent is then evaporated to obtain the positive electrode layer 11. A solid electrolyte layer 28 and a negative electrode layer 31, which are separately prepared, are laminated on the positive electrode layer 11 to obtain the electricity storage device 10.
[0048] Since the source of carrier ions is the active material 18 of the positive electrode layer 11, the theoretical value of the capacity (theoretical capacity) of the electricity storage device 10 obtained when it is discharged is greatly dependent on the capacity of the active material 18. In reality, it is not possible to utilize 100% of the active material 18, so the amount of electricity (discharge capacity) that can actually be extracted from the electricity storage device 10 increases the higher the utilization rate of the active material 18.
[0049] One of the causes of the decrease in the utilization rate of the active material 18 is the thickness of the composite layer 13 (the distance between the interface 14 and the surface 22). In general, the positive electrode layer 11 is more likely to suffer from a shortage of ions as the distance from the surface 22 of the composite layer 13 to which the solid electrolyte layer 28 is in contact increases (as the positive electrode layer 11 approaches the interface 14). In addition, the diffusion rate of ions in the solid electrolyte 15 is slower at the interface (grain boundary) where the particles of the solid electrolyte 15 contact each other than the diffusion rate within the particles. Therefore, in order to facilitate the diffusion of ions within the particles, which have a faster diffusion rate than the interface of the solid electrolyte 15, many first particles 16 having a larger particle size than the second particles 17 are arranged near the interface 14 where the supply of ions is likely to be insufficient.
[0050] However, because the first particles 16 have a larger particle size than the second particles 17, the total area where a plurality of first particles 16 are in direct contact with one active material 18 is smaller than the total area where a plurality of second particles 17 are in direct contact with one active material 18. Therefore, the resistance caused by the movement of ions between the first particles 16 and the active material 18 is larger than the resistance caused by the movement of ions between the second particles 17 and the active material 18 by the amount of the smaller contact area.
[0051] Therefore, the ion conductive material 21 is brought into contact with the first particles 16 and the active material 18, the area of contact between the first particles 16 and the active material 18 is increased via the ion conductive material 21, and the resistance caused by the movement of ions between the first particles 16 and the active material 18 is reduced. This ensures the supply of ions in the composite layer 13 near the interface 14 and prevents a decrease in the reaction of the positive electrode layer 11, thereby increasing the utilization rate of the active material 18.
[0052] Furthermore, since the solid electrolyte 15 (second particles 17) of the second group 24 including the surface 22 of the composite layer 13 is smaller than the solid electrolyte 15 (first particles 16) of the first group 23 including the interface 14, the surface 22 of the composite layer 13 has fewer projections and recesses. This prevents the distance between the electrodes at the projections of the composite layer 13 from becoming shorter when the positive electrode layer 11 and the negative electrode layer 31 are placed face to face. Furthermore, since the electrode reaction occurs dispersedly on the surface 22 of the composite layer 13, damage such as a short circuit in the electricity storage device 10 can be reduced.
[0053] The particles of solid electrolyte 15 contained in the first group 23 have a larger number of first particles 16 having a particle size of 1 μm or more than the particles of solid electrolyte 15 contained in the second group 24, and the particles of solid electrolyte 15 contained in the second group 24 have a larger number of second particles 17 having a particle size of less than 1 μm than the particles of solid electrolyte 15 contained in the first group 23. This makes it easier for ions to diffuse within the particles of solid electrolyte 15 near the current collecting layer 12. This makes it possible to increase the utilization rate of the active material 18. Furthermore, the surface 22 of the composite layer 13 has fewer irregularities, which makes it possible to further reduce damage to the electricity storage device 10.
[0054] The ionic conductor 21 contained in the composite layer 13 includes one or more selected from a liquid, a gel, and a solid. The ionic conductor 21 made of a solid is softer than the solid electrolyte 15 and the active material 18. Therefore, the ionic conductor 21 buffers the stress generated in the composite layer 13 due to the expansion and contraction of the active material 18 accompanying the entry and exit of ions. This makes it possible to reduce the occurrence of peeling at the interface 14 between the current collecting layer 12 and the composite layer 13.
[0055] An ionic liquid having high wettability and high heat resistance with respect to the solid electrolyte 15 is contained in the ionic conductive material 21. This makes it possible to reduce the resistance caused by the movement of ions between the solid electrolyte 15 and the active material 18, while ensuring the heat resistance of the positive electrode layer 11.
[0056] When the solid electrolyte 15 is an oxide-based solid electrolyte, the stability against humidity can be improved. Although the oxide-based solid electrolyte has a large grain boundary resistance, the composite layer 13 includes the ion conductive material 21 that contacts the solid electrolyte 15 and the active material 18, so that the grain boundary resistance of the composite layer 13 can be reduced while the stability against humidity can be improved.
[0057] The volume of the active material 18 in the first group 23 is smaller than the volume of the active material in the second group 24. As a result, the volume of the solid electrolyte 15 and the ionic conductive material 21 in the first group 23 is larger than the volume of the solid electrolyte 15 and the ionic conductive material 21 in the second group 24. As a result, it is possible to reduce the difference between the utilization rate of the active material 18 in the first group 23 and the utilization rate of the active material 18 in the second group 24. This makes it difficult for the positive electrode layer 11 to deteriorate.
[0058] Fig. 3 is a schematic cross-sectional view of the negative electrode layer 31. The negative electrode layer 31 is formed by overlapping a current collecting layer 32 and a composite layer 33. Fig. 3 shows a cross section of the negative electrode layer 31 perpendicular to an interface 34 between the current collecting layer 32 and the composite layer 33. The current collecting layer 32 is a member having electrical conductivity. Examples of materials for the current collecting layer 32 include metals selected from Ni, Ti, Fe, Cu, and Si, alloys containing two or more of these elements, stainless steel, and carbon materials.
[0059] The composite layer 33 includes a solid electrolyte 35, an active material 38, and an ion conductive material 41. The solid electrolyte 35 and the ion conductive material 41 are similar to the solid electrolyte 15 and the ion conductive material 21 included in the positive electrode layer 11 (see FIG. 2), and therefore a description thereof will be omitted. The active material 38 is Li, a Li-Al alloy, Li4Ti5O 12 , graphite, In, Si, a Si—Li alloy, and SiO.
[0060] The composite layer 33 may further include a binder and a conductive assistant. Examples of the binder included in the composite layer 33 include polyimide-based, acrylic-based, polysiloxane, polyalkylene glycol, polyvinylidene fluoride, polytetrafluoroethylene, and styrene-butadiene rubber. Examples of the conductive assistant included in the composite layer 33 include carbon black, acetylene black, ketjen black, carbon fiber, Ni, Pt, and Ag.
[0061] The solid electrolyte 35 contained in the composite layer 33 includes first particles 36 and second particles 37. The first particles 36 are particles having a larger particle diameter than the second particles 37. The particle diameters of the particles 36, 37 refer to the circle equivalent diameter. For example, the particle diameter of the first particles 36 is 1 μm or more and is ½ or less of the thickness of the composite layer 33. The particle diameter of the second particles 37 is less than 1 μm. In the composite layer 33, many of the first particles 36 are arranged near the current collecting layer 32, and many of the second particles 37 are arranged in positions far from the current collecting layer 32.
[0062] The particle group made of solid electrolyte 35 and active material 38 contained in composite layer 33 includes a first group 43 arranged at a position including interface 34 between current collecting layer 32 and composite layer 33, and a second group 44 arranged at a position including surface 42 of composite layer 33. Second group 44 is located between first group 43 and surface 42. In this embodiment, the particle group contained in composite layer 33 includes first group 43 and second group 44. Solid electrolyte layer 28 (see FIG. 1 ) is in contact with surface 42 of composite layer 33.
[0063] The straight lines 45, 46 shown in Fig. 3 are lines drawn on an image of the composite layer 33 acquired by SEM. To ensure the measurement accuracy of the numbers A and B of intersections, the lengths of the straight lines 45, 46 are 50 µm or more and the widths are 1 µm or less. If an image is obtained in which straight lines 45, 46 with a length of 50 µm or more cannot be drawn, the longest straight lines 45, 46 are drawn on that image. The magnification of the image acquired by SEM can be, for example, 3000 times.
[0064] Of the active materials 38 contained in the composite layer 33, the particles 39 are those whose geometric center of cross section is closest to the current collecting layer 32. In this embodiment, the particles 39 are in contact with the current collecting layer 32. The particles 39 are included in a first group 43. The particles 40 are those whose geometric center of cross section is farthest from the current collecting layer 32, among the active materials 38 contained in the composite layer 33. The particles 40 are included in a second group 44.
[0065] The surface 42 of the composite layer 33 is a straight line passing through the point with the longest distance from the interface 34 among the lines indicating the grain boundaries of the particles 40 and parallel to the interface 34. The straight line 45 is a straight line passing through the geometric center of the particle 39 and parallel to the interface 34. The straight line 46 is a straight line passing through the geometric center of the particle 40 and parallel to the interface 34. The straight line 45 crosses the first group 43, and the straight line 46 crosses the second group 44.
[0066] The straight line 47 is a straight line drawn at the position of the boundary between the first group 43 and the second group 44 and parallel to the interface 34. The solid electrolyte 35 and the active material 38 intersecting the straight line 47 are excluded from the particles included in the first group 43 and the second group 44. The straight line 47 exists in the central range among the three ranges formed by dividing the distance between the interface 34 and the surface 42 of the composite layer 33 into three equal parts.
[0067] The first group 43 contains more of the first particles 36 than the second particles 37. The second group 44 contains more of the second particles 37 than the first particles 36. That is, the first group 43 contains more solid electrolytes 35 with a larger particle size than the particle size of the solid electrolyte 35 included in the second group 44. This can be determined by comparing the particle size distribution of the equivalent circle diameter of the solid electrolyte 35 included in the first group 43 and the particle size distribution of the equivalent circle diameter of the solid electrolyte 35 included in the second group 44 through image analysis of the cross-section of the composite layer 33.
[0068] Therefore, the number A of intersections between the straight line 45 and the grain boundaries of the solid electrolyte 35 is less than the number B of intersections between the straight line 46 and the grain boundaries of the solid electrolyte 35. In particular, it is more preferable that the number B is at least twice the number A. The numbers A and B of intersections are measured for images obtained at five or more separate locations in the composite layer 33. The negative electrode layer 31 satisfies the condition of A < B in more than 80% of the five or more images, and more preferably satisfies the condition of 2A ≤ B.
[0069] Five or more images means that there are five or more images in which a portion through which the straight line 45 passes and a portion through which the straight line 46 passes are included in one image. However, when it is not possible to obtain an image in which a portion through which the straight line 45 passes and a portion through which the straight line 46 passes are included in one image, five or more images including a portion through which the straight line 45 passes are prepared, and separately, five or more images including a portion through which the straight line 46 passes are prepared. The numbers A and B are determined from these images.
[0070] In the negative electrode layer 31, the active material 38 is unevenly distributed in the thickness direction of the composite layer 33. Specifically, the volume occupied by the active material 38 in the first group 43 is smaller than the volume occupied by the active material 38 in the second group 44. Therefore, the number C of intersections between the line 45 and the grain boundaries of the active material 38 is smaller than the number D of intersections between the line 46 and the grain boundaries of the active material 38. The lines used to measure the number of intersections (intersections) with the grain boundaries of the active material 38 are not limited to the lines 45 and 46. Any two or more lines (each with a length of 50 μm or more and a width of 1 μm or less) parallel to the interface 34 may be used as long as they intersect with the grain boundaries of the active material 38. The number of intersections between the line that is farther from the interface 34 and the grain boundaries of the active material 38 is greater than the number of intersections between the line that is closer to the interface 34 and the grain boundaries of the active material 38.
[0071] The negative electrode layer 31 can be manufactured by a method similar to that of the positive electrode layer 11. Like the positive electrode layer 11, the negative electrode layer 31 can increase the utilization rate of the active material 30 and reduce damage such as a short circuit of the electricity storage device 10. Other effects of the negative electrode layer 31 are also similar to those of the positive electrode layer 11.
[0072] The present invention has been described above based on an embodiment, but the present invention is in no way limited to the above embodiment, and it can be easily inferred that various improvements and modifications are possible within the scope of the present invention without departing from the spirit of the present invention.
[0073] In the embodiment, the positive electrode layer 11 in which the composite layer 13 is provided on one side of the current collecting layer 12, and the negative electrode layer 31 in which the composite layer 33 is provided on one side of the current collecting layer 32 have been described as electrodes, but the present invention is not necessarily limited to this. For example, it is of course possible to apply each element in the embodiment to an electrode in which the composite layer 13 and the composite layer 33 are provided on both sides of the current collecting layer 12 (a so-called bipolar electrode). If the bipolar electrodes and the solid electrolyte layer 28 are alternately stacked and housed in a single container, a so-called bipolar structure electricity storage device can be obtained.
[0074] In the embodiment, the case where the solid electrolyte 15 and the active material 18 contained in the composite layer 13 of the positive electrode layer 11 are composed of the first group 23 including the interface 14 and the second group 24 including the surface 22 has been described, but this is not necessarily limited to this. It is naturally possible to provide another particle group composed of the solid electrolyte 15 and the active material 18 between the first group 23 and the second group 24. Similarly, in the negative electrode layer 31, it is naturally possible to provide another particle group composed of the solid electrolyte 35 and the active material 38 between the first group 43 and the second group 44. The other particle group is a particle group having a particle size distribution that is not related to the particle size distribution of the solid electrolyte contained in the first group 23, 43 or the second group 24, 44. It is preferable that the other particle group has a particle size distribution intermediate between the particle size distribution of the solid electrolyte contained in the first group 23, 43 and the particle size distribution contained in the second group 24, 44.
[0075] In the embodiment, the ionically conductive carrier is Li + In the above description, the electric storage device 10, the positive electrode layer 11, and the negative electrode layer 31 are configured as carriers of Li, but the present invention is not limited to this. + Of course, it is possible to use other carriers than the above. Other carriers include alkaline earth metal ions and Na + Alkali metal ions such as Ag + ,Cu + In the embodiment, a secondary battery has been described as an example of the power storage device 10, but the present invention is not limited to this. It is of course possible to apply the present invention to other power storage devices such as capacitors and their electrodes. [Explanation of symbols]
[0076] 10. Energy storage devices 11 Positive electrode layer (electrode) 12 Current collecting layer 13 Composite layer 14 Interface 15 Solid electrolyte 16 The First Particle 17 Second Particle 18 Active material 21 Ion Conductive Materials 22 Surface 23 Group 1 24 Group 2 31 Negative electrode layer (electrode) 32 Current collecting layer 33 Composite layer 34 Interface 35 Solid electrolyte 36 First Particle 37 Second Particle 38 Active material 41 Ion Conductive Materials 42 Surface 43 Group 1 44 Group 2
Claims
1. A current collecting layer and a composite layer, The composite layer is an electrode including a solid electrolyte and an active material, the composite layer further includes an ion conductive material in contact with the solid electrolyte and the active material, the particle group made of the solid electrolyte and the active material includes a first group arranged at a position including an interface between the current collecting layer and the composite layer, and a second group arranged at a position including a surface of the composite layer and located between the first group and the surface, the first group contains a large amount of solid electrolytes having a particle size larger than that of the solid electrolytes contained in the second group; The solid electrolyte particles contained in the first group have a larger number of particles having a particle size of 1 μm or more than the solid electrolyte particles contained in the second group, and the solid electrolyte particles contained in the second group have a larger number of particles having a particle size of less than 1 μm than the solid electrolyte particles contained in the first group; The ion conductive material is an electrode containing an ionic liquid having ion conductivity.
2. 2. The electrode according to claim 1, wherein a volume of the active material in the first group is smaller than a volume of the active material in the second group.
3. An electricity storage device comprising the electrode according to claim 1 or 2.
Citation Information
Patent Citations
Sulfide solid battery
JP2019212430A
Ion conductor and power storage device
JP2020145009A
All-solid-state lithium-ion secondary battery
WO2014132333A1